A patient-level pooled analysis of treatment-shortening regimens for drug-susceptible pulmonary tuberculosis. (November 2018) - Imperial, Marjorie; Nahid, Payam; Phillips, Patrick; Davies, Geraint; Fielding, Katherine; Hanna, Debra; Hermann, David; Wallis, Robert; Johnson, John; Lienhardt, Christian; Savic, Rada
Abstract Tuberculosis kills more people than any other infectious disease. Three pivotal trials testing 4-month regimens failed to meet non-inferiority margins; however, approximately four-fifths of participants were cured. Through a pooled analysis of patient-level data with external validation, we identify populations eligible for 4-month treatment, define phenotypes that are hard to treat and evaluate the impact of adherence and dosing strategy on outcomes. In 3, 405 participants included in analyses, baseline smear grade of 3+ relative to <2+, HIV seropositivity and adherence of ≤90% were significant risk factors for unfavorable outcome. Four-month regimens were non-inferior in participants with minimal disease defined by <2+ sputum smear grade or non-cavitary disease. A hard-to-treat phenotype, defined by high smear grades and cavitation, may require durations >6 months to cure all. Regimen duration can be selected in order to improve outcomes, providing a stratified medicine approach as an alternative to the 'one-size-fits-all' treatment currently used worldwide. Analysis of tuberculosis drug trials identifies features to stratify patients for longer or shorter treatment duration than the standard of care, in order to improve therapeutic outcomes.